ANALISA DAYA DUKUNG FONDASI TIANG TUNGGAL DENGAN DATA SPT - Lestari, Asih Mitra Fenie (Lambung Mangkurat University Press, 2023)
Analysis of the bearing capacity of foundations requires investigation of adequate soil data and selection of the appropriate bearing capacity calculation method to minimize errors in planning. Soil investigations carried out in this paper include deep drilling and SPT tests, as well as laboratory tests. In calculating the bearing capacity of the pile, the N-SPT value is used which has been corrected for the SPT hammer energy, as well as corrections for the ground water level and overburden pressure. Soil investigations were carried out at the planned location of the Palm Oil Factory in Branch Village River, Keamatan. Kumai, Kabupaten Pangkalan Bun. The test results show that there is a very soft to soft cohesive soil layer at a depth of around 8.00 – 18.00 m. Hard soil layers began to be found at a depth of 45.00 m until the end of the test depth at 50.00 m. The planned pile foundation is a spun pile with a diameter of 500 m with an embedded pile length of 46.00 m. The calculation method used is Meyerhoff (1956), Briaud et al. (1985), and Decourt (1987). With Safety Factor 3, the average permitted carrying capacity is 183.90 tons (Meyerhoff Method, 1956), 153.07 tons (Briaud et al., 1985 Method), and 156.75 tons (Decourt, 1987). The ultimate bearing capacity using the Meyerhoff (1956) method is approximately 15% greater than that of the other two methods.